Literature Review: Implementation of Cooperative Learning Model in Civics Learning To Increase the Activeness of Elementary School Students - Wisista , Nugraha Widya; Widyawati, Restina Salsabilla Eka; Puspitasari, Yuliana Putri; Rawanoko, Endrise Septina (CAKRAWALA: Journal of Citizenship Teaching and Learning, 2024)
The purpose of writing this review article is; 1) to find out the application of learning models that foster student collaboration in Citizenship Education subjects, and 2) to find out the appropriate learning model in increasing student activeness in Citizenship Education subjects. To review the articles found using the Systematic Literature Review (SLR) method. Articles were reviewed that were sourced from the Google Scholar database with a time span of the last 3 years from 2021 to 2024. Of the several articles found, there are 3 articles as the final result that have gone through the screening and extraction process and will be analyzed. The results of the article review are; 1) the learning model can increase student learning activities after the application of the Cooperative Learning learning method in the Civic Education subject, 2) Cooperation among students during the learning process can naturally generate communication, which in turn can make students more involved and ultimately facilitate the process of discovery, understanding, and mastery of ideas, 3) the application of cooperative learning in Civics learning increases students' activities, makes them more creative, active, and motivated, and strengthens individual and group cooperation and responsibility.